Partitioning of polycyclic aromatic hydrocarbons in heterogeneous clusters - Bowal, Kimberly (2019)
The morphologies of heterogeneous clusters of polycyclic aromatic hydrocarbons (PAHs) are investigated using molecular modelling. Clusters of up to 100 molecules containing combinations of the different sized PAHs circumcoronene, coronene, ovalene, or pyrene are evaluated. Replica exchange molecular dynamics simulations using an all-atom force field parameterised for PAHs sample many configurations at high and low temperatures to determine stable low energy structures. The resulting cluster structures are evaluated using molecular radial distances and coordination numbers, and are found to be independent of initial configuration and the cluster sizes studied. Stable clusters consist of stacked PAHs in a core-shell structure, where the larger PAHs are found closer to the cluster core and the smaller PAHs are located on the cluster surface. This work provides novel insight into the molecular partitioning of heterogeneous aromatic clusters, with particular relevance to the structure of nascent soot particles.